Abstract State Machines - Theory and Applications : International Workshop, ASM 2000 Monte Verita, Switzerland, March 19 24, 2000 Proceedings - Gurevich, Yuri; Kutter, Philipp W.; Odersky, Martin; Thiele, Lothar (Lecture notes in computer science ;, 2000)
This book constitutes the thoroughly refereed post-proceedings of the International Workshop on Abstract State Machines, ASM 2000, held in Monte Verita, Switzerland in March 2000. The 12 revised full papers presented were carefully reviewed and selected from 30 submissions. Also included are an introductory overview, two reports on industrial ASM applications, as well as six contributions based on invited talks. All in all, the volume competently presents the state of the art in research and applications of abstract state machines.